A second documented record of Spectacled Petrel Procellaria conspicillata in Argentine waters - Seco Pon, Juan Pablo (2015)
The Spectacled Petrel Procellaria conspicillata is endemic to Inaccessible Island, in the Tristan da Cunha group (central South Atlantic). The species is considered an occasional visitor to Argentina and there are few records of the species in national waters. On 13 February 2014, two birds were observed (and photographed) 89 nautical miles southeast off Buenos Aires Province at 38°55'S, 56°00'W. This record represents the second documented record of Spectacled Petrel for Argentina.